Maximizing the enterprise information assets - Wells, Timothy D. (Auerbach Publications, 2003)
The ramifications of this new Information Age are still not well understood. Most businesses do not know how to turn their information into a beneficial capital asset. Unfortunately, their focus has been almost exclusively on technology, while human and managerial factors are left unexplored. Maximizing the Enterprise Information Assets defi.